IMPLEMENTATION OF HEALTH PROTOCOLS DURING COVID-19 PANDEMIC IN PONDOK PESANTREN IN THE SPECIAL REGION OF YOGYAKARTA - Yanasta Yudo Pratama; Fajrul Falah Farhany; Ichlasul Amalia; Nailul Husna; Vita Widyasari (Universitas Airlangga, 2022)
Introduction: COVID-9 is a global pandemic and causes changes in behavior and life. The implementation of health protocols is the most important aspect to prevent the transmission of COVID19, especially in the Islamic boarding schools (Pondok Pesantren) community. The aim of this study is to identify the practice of a clean and healthy lifestyle as well as the application of health protocols in the Pondok Pesantren to control the spread of COVID-19. Methods: The preliminary survey was conducted as a part of training for the healthy student cadre and the establishment of COVID-19 shelters in Pondok Pesantren in The Special Region of Yogyakarta, Indonesia. Fourteen questions including the name of Pondok Pesantren and multiple-choice questions related to clean and healthy living behaviors comparison before and during the pandemic, health protocol implementation during the pandemic, and provision of COVID-19 prevention and control program. Results: Total sample consisted of 84 students from 18 Pondok Pesantren in The Special Region of Yogyakarta. Among the factors affecting the student’s compliance with health protocol implementation in Pondok Pesantren were the disparity of individual’s understanding and obedience to rules and regulations regarding health protocol implementation (71,8%), inadequate facilities (12,8%), and other factors including that there was no strict supervision and punishment for violation upon regulations. Conclusion: Pondok pesantren is an institution that needs more attention amid the pandemic of COVID-19. Dense population, minimum infrastructure, and relatively poor access to healthcare facilities have made them a vulnerable community.